2018
DOI: 10.31529/sjms.2018.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Privatization a Panacea? Pre and Post Privatization Analysis of Financial Performance

Abstract: The aim of this study is to examine the impact of privatization of state-owned enterprise on financial performance, employees' satisfaction and customer satisfaction. Pakistan Telecommunication Company Limited (PTCL) was taken as the organization for analysis. Five years pre and post-privatization financial figures were analyzed to compare the return on asset, return on equity, earning per share, net profit margin, and dividend payout. To know customer satisfaction level, the questionnaire was personally admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…The selected Nepalese commercial banks observed growth in net profit as well as asset size after the merger. However, Miko (2010), Pathak (2016), and Khan et al (2017) did not find a significant effect of the merger on ROA. It was established from this study that there is no significant difference in pre-and post-merger ROE, which is in accordance with the results of Nanda (2016), Dwa and Shah (2017), and Dewi and Mustanda ( 2021), but Fatima and Shehzad (2014) and Bipin et al (2018) found contradicting evidence.…”
Section: Discussionmentioning
confidence: 93%
“…The selected Nepalese commercial banks observed growth in net profit as well as asset size after the merger. However, Miko (2010), Pathak (2016), and Khan et al (2017) did not find a significant effect of the merger on ROA. It was established from this study that there is no significant difference in pre-and post-merger ROE, which is in accordance with the results of Nanda (2016), Dwa and Shah (2017), and Dewi and Mustanda ( 2021), but Fatima and Shehzad (2014) and Bipin et al (2018) found contradicting evidence.…”
Section: Discussionmentioning
confidence: 93%
“…For example, privatization increases workers' psychological stress and is significantly associated with poor job performance in Thailand. Moreover, employees of large healthcare providers in Canada experience higher stress and delay due to reduced job control following privatization Khan et al (2012).…”
Section: Literature Reviewmentioning
confidence: 99%